2022
DOI: 10.1002/nop2.1411
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between nurses' resilience and depression, anxiety and stress during the 2021 COVID‐19 outbreak in Taiwan

Abstract: Aim The COVID‐19 outbreak in Taiwan had a significant impact on medical services. These changes posed a threat to nurses' mental health. Resilience may protect nurses from the psychological impact of COVID‐19. This study aimed to understand nurses' resilience and its relationship with nurses' characteristics (life and work situations) and mental health (depression, anxiety and stress) during the outbreak. Design A cross‐sectional study. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The results of this study are different from studies by Foster et al [ 30 ] on mental health nurses in Australia which show a significant relationship between resilience and length of service. According to research by Wu et al [ 31 ], nurses with more than 15 years of experience were more resilient. About 31% of the nurses in this study with fewer than 15 years of experience reported having low resilience.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are different from studies by Foster et al [ 30 ] on mental health nurses in Australia which show a significant relationship between resilience and length of service. According to research by Wu et al [ 31 ], nurses with more than 15 years of experience were more resilient. About 31% of the nurses in this study with fewer than 15 years of experience reported having low resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Individual, semi‐structured interviews were conducted with each participant. According to Husserl (Sundler et al., 2019; Wu et al., 2023), this design is suitable for exploring participants' life experiences and gaining an understanding of their individual perspectives. The training hospital is situated in the north‐east of Namibia and serves as a referral hospital for three regions, which have a combined population of approximately half a million people.…”
Section: Methodsmentioning
confidence: 99%
“…As is common in phenomenological studies, data were collected through in‐depth individual interviews which were conducted according to an interview guide (Wu et al., 2023). The data were collected during August and September 2022.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These interventions aim to promote positive psychological functioning and well-being, particularly in the face of stress and adversity (Hasan et al, 2022). For instance, psychological resilience-building interventions have been found to be effective in promoting resilience and reducing depression, anxiety, and stress among healthcare workers during the COVID-19 pandemic (Wu et al, 2022). Additionally, fostering personal resources such as optimism, hope, courage, trait mindfulness, and self-efficacy has been identified as a key strategy for enhancing psychological resilience (Chiesi et al, 2022).…”
Section: Psychological Approaches To Building Resiliencementioning
confidence: 99%